Collaboration at International, National and Institutional Level – Vital in Fostering Open Science - Hormia-Poutanen, Kristiina; Forsström, Pirjo-Leena (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Open science and open research provide potential for new discoveries and solutions to global problems, thus are automatically extending beyond the boundaries of an individual research laboratory. By nature they imply and lead to collaboration among researchers. This collaboration should be established on all possible levels: institutional, national and international. The present paper looks at the situation in Finland, it shows how these collaborations are organized at the various levels. The special role played by LIBER is evidenced. The advantages of these collaborations are highlighted.